Chronoamperometric Evaluation of the Antioxidantcapacity of Micellar Spice Extracts - G.K. Ziyatdinova; E.R. Ziganshina; Ph. Nguyen Cong; H.C. Budnikov (Учёные записки Казанского университета: Серия Естественные науки, 2015)
The oxidation potentials of micellar spice extracts on a glassy carbon electrode modified with cerium dioxide nanoparticles in the Brij®35 micellar medium in phosphate buffer solution have been found. A chronoamperometric approach for evaluation of the antioxidant capacity (AOC) of micellar spice extracts based on the oxidation of their antioxidants under the conditions of potentiostatic electrolysis at 1.1 V has been developed. It has been shown that steady-state electrolysis is attained in 100 s. The AOC has been expressed in gallic acid equivalents recalculated per 1 g of dry spices. The dynamic analytical range of gallic acid was 7.50–2500 μM with the limits of detection and quantification of 2.27 and 7.50 μM, respectively. The approach has been tested on the extracts of 20 spices. Their AOC varied in a wide range (from 109.0 ± 0.2 mg/g for clove to 1.9 ± 0.1 mg/g for caraway) owing to the composition and contents of active components in raw plant materials. Positive correlations have been found between the AOC of spices and their antioxidant activity based on the reaction with 2,2-diphenyl-1-picrylhydrazyl (r = 0.8990 at rcrit = 0.497) and ferric reducing power (r = 0.9066 at rcrit = 0.497).